THE BENEFITS OF A BINDER IN THE POSTOPERATIVE PERIOD OF ABDOMINAL SURGERY: AN INTEGRATIVE LITERATURE REVIEW - Ramos, Tiago; Topa, Paula; Carvalho, Ana; Castro, Carla; Moreira, Helena; Martins , Andréia; Alves, Sofia (Health and Society, 2023)
Introduction: Postoperative complications are a reality in the context of abdominal surgery, which is why the use of an abdominal bandage was strongly recommended for decades. Objectives: The aim is to identify the benefits for the patient and verify the pertinence of the recommendation for its use, taking into account the advancement of surgical techniques. Methodology: A integrative review of the literature was carried out, in which studies from 2017 to 2022 were identified in the database aggregators EBSCOhost (CINAHL Complete, MEDLINE Complete, Nursing & Allied Health Collection, Cochrane Plus Collection) and Web of Science (SciELO). Results: 137 articles were identified, of which 15 were included for review. Discussion: In the literature, several benefits are pointed out with the use of abdominal bandage, namely in the healing of the surgical wound, in comfort and in early mobilization. However, it was in pain control that there was greater benefit for patients in most articles. Considering these factors, the patient becomes more cooperative in performing recovery exercises. Conclusion: Current scientific evidence indicates that abdominal taping, when correctly applied, is an effective strategy that favors the functional recovery of patients undergoing abdominal surgery by laparotomy.